Generating crosslinking network in XNBR based on copper (I)–carboxylate interaction. (30th November 2022) - Wajge, Suraj W.; Das, Chayan
Abstract: Carboxylated nitrile rubber (XNBR) is crosslinked via metal–ligand coordination bond by simple mixing and compounding as an alternate to chemically rich traditional vulcanization route. Basis of the generation of reversible non‐covalent crosslinks, in the rubber matrix, is copper (I)–carboxylate metal–ligand interaction that is evidenced by XPS, FTIR, and rheological studies. At low copper content (5 phr), self‐healing property is exhibited by the composite while adequate mechanical strength is obtained at higher copper content (20 phr). For 20 phr filled composite (XNBR–Cu20), the tensile strength reaches up to 5.41 ± 0.28 MPa, which is almost 19 times higher than that of pure XNBR (0.29 ± 0.02 MPa). On the other hand, tensile strength is not so high (1.95 ± 0.20 MPa) for composite XNBR–Cu5, however, this one shows the self‐healing efficiency of around 75% for the first cycle, 71% for second cycle, and 56% for the third cycle. The positive shift of glass transition temperature ( T g ) takes place with the increasing content of copper (I)–carboxylate crosslinking that is caused by the lowering in segmental mobility of the rubber chains. Reversible nature of the metal–ligand coordination, recoverability, and hysteresis in the XNBR–Cu (I) composite are studied by cyclic stress–strain loading. The CuCl content greatly influences the inherent crosslinking nature of the elastomeric network and the ultimate properties of the composites.